Pilon fracture of the tibia with severe complications in a 42-year-old patient - case report. - Artur Daniel Dziedzic; Bartosz Potoczniak; Marcin Bąk; Tomasz Blicharski; Urszula Dziedzic; Teresa Małecka-Massalska; Jaromir Jarecki (Kazimierz Wielki University, 2019)
Pilon type fractures of the distal tibia are among the most difficult injuries of the lower extremity. They occur due to the axial loading injury which drives the talus into the tibial plafond, mainly because of high energy traumas such as car accidents and falls, but may arise from low energy traumas also. Due to specific conditions in the area of the injury: where skin and subcutaneous tissue is delicate, soft tissues are usually severely damaged, it is crucial to choose the correct timing for surgical intervention. There are several surgical options regarding treatment of the pilon fractures, however treatment plan of pilon fractures has not yet been unified. Surgical methods include open reduction with internal fixation and external fixation. Main purpose of the treatment of pilon fractures are the preservation of length and restoration of the joint surfaces. Great risks for the successful treatment are skin and soft tissue infections, that occur quite commonly due to specific anatomy of the fractured area. Wound infection may have potentially catastrophic consequences. Here we present a case of our 42-year-old patient, with a pilon fracture of the tibia who suffered multiple complications due to obtained tauma as well as his concurrent diseases: diabetes, alcohol and nicotine abuse, also as a result of his lack of compliance with medical advice. Despite the complications that occurred, outcome of the overall treatment was satisfactory both to the patient as well as orthopedic team. This example shows that treatment method should be chosen wisely not only on the type of the fracture, but also with patient's ability to comply with doctors' recommendation.